مستوى ترجمة معاني الكلمات العربية لدى طلبة الشهادة العالية الدينية الماليزية - Izzah Syakirah Maaruf; Rosni Samah (Usuli Faqih Research Centre PLT, 2024)
The number of STAM candidates getting mumtaz results increases every year, but the number of candidates who fail the “Imtihan Qabul” exam at Al-Azhar University is also increasing. Therefore, this study was conducted to identify the vocabulary translation level skills consisting of names, verbs, and conjunctions among sixth grade students at one of the religious schools in Selangor. Researchers use frequency analysis to obtain percentages. A total of 80 respondents were randomly selected to answer a set of questions by translating 66 Arabic vocabulary selected from STAM learning textbooks. Frequency analysis results shows that respondents' translation level for nouns, verbs, and conjunctions is weak. This study suggests that translation exercises are conducted periodically for students whether in the classroom or in co-curricular activities.